Patient enablement and satisfaction towards the service given by the doctors in UTM medical centre - Nurul Jamilah Muhamad 1992 author 638211; Norzaidahwati Zaidin, 1967- 614995; Fakulti Pengurusan 538641 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2016